An in-depth analysis of the Terrorists Activities on Land Use and Land Cover (LULC) Change of Sambisa Forest of Nigeria (American Journal of Geospatial Technology, 2025)
This study analyzed terrorists activities on land use and land cover change of Sambisa Forest of Nigeria. Land use and land cover change was employed to determine the rate of change in Sambisa Forest as a result of Boko Haram activities. GIS and remote sensing was employed in the course of this study. Secondary types and sources of data were used and they include data on the vegetation cover of Sambisa Forest before and during the emergence of Boko Haram and data on the land use/land cover. The data for the vegetation analysis of this study were obtained using satellite imageries of the study area from 1994, 1999, 2004, 2009, 2014 and 2019. The Landsat images of each year was independently classified with supervised classification technique. Each analysis carried out was subjected to different formular for deducing each of the variables. Maximum likelihood classifier algorithm was applied to classify the LULC types in QGIS 3.8.2 software. The result from satellite imagery analysis for land use land cover of Sambisa forest for the year 1994 revealed that marshland constitutes 13.4% amounting to 63.4km2 on the satellite image. Vegetation measurement on the satellite image covers an area of 222.38km2 representing 46.9%. Bare surface covers an area of 84.01km2 representing 17.7% of the imagery. Built-up accounts for 21.2% covering an area of 100.6km2, such settlements include; Masba, Dalwa, Dalori, Bama, Konduga, Tateri, Kuka Kowa, among others. Water (lakes, ponds, streams, etc.) amounted to 0.76% covering an area of 3.61km2. The year 2009 witnessed the beginning of the vicious cycle of violence starting from Borno State, around the Sambisa forest northern corridor of Konduga, Bama Dalori and ultimately Maiduguri. From the analysis, the result experienced a fluctuating dip and rise with water bodies accounting for 0.66% of the total landcover with an area coverage of 3.12km2 comparing this result with that of 2004 which was 0.5% (2.17km2), this simply means that there was a slight increase by 0.16% which accounted for the rise. Bare surface cover in the area was 20.6% representing 97.6km2 precisely areas around Konduga. Marshland in the area accounted for 19.1% representing 90.7km2. There was an increase in the vegetation of the study from 104.13 the previous year to 201.5 in 2009. Land use land cover analysis for 2019 yielded another interesting result leaving little to doubt from the previous years. From the analysis, Water occupied 0.39% representing 1.86km2, vegetation within the area had 11.61% which is a drop from the 28.5% in the previous year. Marshland covered 32.7%, translating to 155km2; Bare surface accounted for 32.1%, covering an area of 152.10km2, while Built-up had a drastic increase of 23.2%, representing 110.3km2 of the total area. This is a clear indication of Boko Haram activities and Military counter insurgency on Sambisa forest. From the findings, it is recommended that the military should stop Boko Haram activities and force them out of the forest and the area will regenerate and the soil remediated.This study analyzed terrorists activities on land use and land cover change of Sambisa Forest of Nigeria. Land use and land cover change was employed to determine the rate of change in Sambisa Forest as a result of Boko Haram activities. GIS and remote sensing was employed in the course of this study. Secondary types and sources of data were used and they include data on the vegetation cover of Sambisa Forest before and during the emergence of Boko Haram and data on the land use/land cover. The data for the vegetation analysis of this study were obtained using satellite imageries of the study area from 1994, 1999, 2004, 2009, 2014 and 2019. The Landsat images of each year was independently classified with supervised classification technique. Each analysis carried out was subjected to different formular for deducing each of the variables. Maximum likelihood classifier algorithm was applied to classify the LULC types in QGIS 3.8.2 software. The result from satellite imagery analysis for land use land cover of Sambisa forest for the year 1994 revealed that marshland constitutes 13.4% amounting to 63.4km2 on the satellite image. Vegetation measurement on the satellite image covers an area of 222.38km2 representing 46.9%. Bare surface covers an area of 84.01km2 representing 17.7% of the imagery. Built-up accounts for 21.2% covering an area of 100.6km2, such settlements include; Masba, Dalwa, Dalori, Bama, Konduga, Tateri, Kuka Kowa, among others. Water (lakes, ponds, streams, etc.) amounted to 0.76% covering an area of 3.61km2. The year 2009 witnessed the beginning of the vicious cycle of violence starting from Borno State, around the Sambisa forest northern corridor of Konduga, Bama Dalori and ultimately Maiduguri. From the analysis, the result experienced a fluctuating dip and rise with water bodies accounting for 0.66% of the total landcover with an area coverage of 3.12km2 comparing this result with that of 2004 which was 0.5% (2.17km2), this simply means that there was a slight increase by 0.16% which accounted for the rise. Bare surface cover in the area was 20.6% representing 97.6km2 precisely areas around Konduga. Marshland in the area accounted for 19.1% representing 90.7km2. There was an increase in the vegetation of the study from 104.13 the previous year to 201.5 in 2009. Land use land cover analysis for 2019 yielded another interesting result leaving little to doubt from the previous years. From the analysis, Water occupied 0.39% representing 1.86km2, vegetation within the area had 11.61% which is a drop from the 28.5% in the previous year. Marshland covered 32.7%, translating to 155km2; Bare surface accounted for 32.1%, covering an area of 152.10km2, while Built-up had a drastic increase of 23.2%, representing 110.3km2 of the total area. This is a clear indication of Boko Haram activities and Military counter insurgency on Sambisa forest. From the findings, it is recommended that the military should stop Boko Haram activities and force them out of the forest and the area will regenerate and the soil remediated.